2018
DOI: 10.1590/1678-7757-2017-0500
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and bacterial load in saliva and dental biofilm of type 1 diabetics on continuous subcutaneous insulin infusion

Abstract: Objectives Since most of the studies evaluates diabetics on multiple daily injections therapy and continuous subcutaneous insulin infusion may help gain better metabolic control and prevent complications, the objective of this study was to evaluate the prevalence of dental caries, the unstimulated salivary flow rate and the total bacteria load, Streptococcus spp. levels and Lactobacillus spp. levels in saliva and supragingival dental biofilm of type 1 diabetics on insulin pump.Material and Methods Sixty patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the studies were conducted in India, eight in the United States, six in Brazil, five in Finland, four each in Portugal, Sweden, and Turkey, two in Lithuania, one each in Belgium, Bosnia and Herzegovina, China, Egypt, Germany, Hungary, Iraq, Jordan, Republic of Kosovo, Kuwait, Libya, Malaysia, Mexico, Spain, Sudan, Thailand, and Uruguay…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… RA, rheumatoid arthritis; SLE, systemic lupus erythematosus. a Ganesan et al (2017). b de Groot et al (2017). c Xiao et al (2017). d Anbalagan et al (2017). e Coelho et al (2018). f Zhou et al (2013). g Corrêa et al (2017). h Corrêa et al (2018, unpublished results). i Queiroz-Junior et al (2011). j Zhang et al (2015). k Corrêa et al (2016). …”
Section: Changes In the Oral Microbiota Caused By Diabetesmentioning
confidence: 94%
“…Screening and preventive treatment are necessary to avoid dental caries before they become incurable in the high-risk population. However, the exact prevalence of dental caries remains controversial in children and adolescents with type 1 diabetes [14–17], especially in those with poor metabolic control [18]. Previous studies reported that the prevalence of dental caries in children and adolescents varies between 36% in Iran [19] and 92% in Chile [20].…”
Section: Introductionmentioning
confidence: 99%